Cardiac myosin binding protein-C phosphorylation regulates the super-relaxed state of myosin - McNamara, James W. (Proc Natl Acad Sci U S A, 2019)
Phosphorylation of cardiac myosin binding protein-C (cMyBP-C) accelerates cardiac contractility. However, the mechanisms by which cMyBP-C phosphorylation increases contractile kinetics have not been fully elucidated. In this study, we tested the hypothesis that phosphorylation of cMyBP-C releases myosin heads from the inhibited super-relaxed state (SRX), thereby determining the fraction of myosin available for contraction. Mice with various alanine (A) or aspartic acid (D) substitutions of the three main phosphorylatable serines of cMyBP-C (serines 273, 282, and 302) were used to address the association between cMyBP-C phosphorylation and SRX. Single-nucleotide turnover in skinned ventricular preparations demonstrated that phosphomimetic cMyBP-C destabilized SRX, whereas phospho-ablated cMyBP-C had a stabilizing effect on SRX. Strikingly, phosphorylation at serine 282 site was found to play a critical role in regulating the SRX. Treatment of WT preparations with protein kinase A (PKA) reduced the SRX, whereas, in nonphosphorylatable cMyBP-C preparations, PKA had no detectable effect. Mice with stable SRX exhibited reduced force production. Phosphomimetic cMyBP-C with reduced SRX exhibited increased rates of tension redevelopment and reduced binding to myosin. We also used recombinant myosin subfragment-2 to disrupt the endogenous interaction between cMyBP-C and myosin and observed a significant reduction in the population of SRX myosin. This peptide also increased force generation and rate of tension redevelopment in skinned fibers. Taken together, this study demonstrates that the phosphorylation-dependent interaction between cMyBP-C and myosin is a determinant of the fraction of myosin available for contraction. Furthermore, the binding between cMyBP-C and myosin may be targeted to improve contractile function.